Novel Form of Curcumin Improves Endothelial Function in Young, Healthy Individuals: A Double-Blind Placebo Controlled Study - Jonathan M. Oliver; Lee Stoner; David S. Rowlands; Aaron R. Caldwell; Elizabeth Sanders; Andreas Kreutzer; Joel B. Mitchell; Martin Purpura; Ralf Jäger (Journal of Nutrition and Metabolism)
Curcumin, a turmeric extract, may protect against cardiovascular diseases by enhancing endothelial function. In this randomized controlled double-blind parallel prospective study, fifty-nine healthy adults were assigned to placebo, 50 mg (50 mg), or 200 mg (200 mg) curcumin, for 8 weeks. The higher curcumin (200 mg) supplementation produced a dose-mediated improvement in endothelial function measured by flow-mediated dilation (FMD). The outcome was a clinically substantial 3.0% increase (90% CI 0.7 to 5.3%, p=0.032; benefit : harm odds ratio 546 : 1) with the 200 mg dose, relative to placebo. The 50 mg dose also increased FMD relative to placebo by 1.7% (−0.6 to 4.0%, p=0.23; 25 : 1), but the outcome was not clinically decisive. In apparently healthy adults, 8 weeks of 200 mg oral curcumin supplementation resulted in a clinically meaningful improvement in endothelial function as measured by FMD. Oral curcumin supplementation may present a simple lifestyle strategy for decreasing the risk of cardiovascular diseases. This trial was registered at ISRCTN registry (ISRCTN90184217).